AUSTRALIAN SPORTS DIPLOMACY TOWARDS ASIA-TAKE THE BASKETBALL ENGAGEMENT AS AN EXAMPLE - Xia, Menghu; Xia, Ting (Universitas Pendidikan Indonesia, 2023)
This study aims to analyze Australian sports diplomacy toward Asia. According to the sports diplomacy expert Dr. Stuart Murray,